Alternative Model of Personality Disorders (DSM-5) Predicts Dropout in Inpatient Psychotherapy for Patients With Personality Disorder - Busmann, Mareike; Wrege, Johannes; Meyer, Andrea H.; Ritzler, Franziska; Schmidlin, Moira; Lang, Undine E.; Gaab, Jens; Walter, Marc; Euler, Sebastian (Frontiers in Psychology, 2019)
Objective: Criterion A serves as the fundamental diagnostic criterion of the Alternative Model of Personality Disorders in section III of the Diagnostic and Statistical Manual 5. Consisting of a self- and an interpersonal dimension, it defines the construct of personality functioning as a general and dimensional factor of personality disorders. This study aimed to explore criterion A along with well-established treatment dropout predictors, e.g., sociodemographic factors, personality disorder diagnosis, symptom severity, and the therapeutic alliance. Method: The sample consisted of 132 patients in a personality disorder specific psychotherapeutic inpatient treatment. Cox proportional hazard regression models and a lasso model were applied. Results: 28% of the sample prematurely discontinued treatment. The risk for dropout was 2.3 times higher for patients with high impairments in self-functioning as assessed with criterion A. Moreover, a positive therapist-rated therapeutic alliance was associated with a lower dropout risk. Conclusion: The study suggests criterion A is a useful clinical indicator by identifying personality disorder patients with a higher risk for dropout. An individualized therapeutic approach for such patients might be required.